From caution to guidance: a narrative review of CrossFit during pregnancy - Petr Schlegel (Termedia Publishing House, 2024)
Public opinion on engaging in vigorous activity during pregnancy remains divided. While numerous examples exist of pregnant women competing at high levels in sports, concerns persist regarding potential adverse effects on maternal and foetal health. CrossFit, known for fostering community and social connection, often remains a continued practice for female athletes during pregnancy, despite its association with high-intensity exercise, Olympic weightlifting, and dynamic movements. This article aims to synthesise current evidence-based information on CrossFit training during pregnancy, objectively outline potential risks, and provide practical recommendations. A narrative review was conducted, sourcing data from PubMed, Scopus, and Semantic Scholar. Articles were categorised into relevant sections: exercise during pregnancy, high-intensity exercise, resistance training, injuries in CrossFit, and practical applications. In the absence of studies directly assessing CrossFit's impact on pregnant women, available sources allow us to endorse this form of exercise as safe and beneficial for both maternal and foetal health. Certain exercises, such as jumping and burpees, should be adapted to the specific trimester, while others might be best avoided (such as box jumps and bar muscle-ups). Nonetheless, adherence to professional guidance and medical directives is crucial. The recommendations herein are intended for healthy, physically active pregnant women.